Properties of individual S-bursts observed in the frequency band of 10–32 MHz during the rising phase of 25-th solar cycle - Dorovskyy, V. V.; Melnik, V. N.; Brazhenko, A. I.; Frantsuzenko, A. V. (Frontiers in Astronomy and Space Sciences, 2024)
Introduction: The properties of the S-bursts observed during the storm on 20–21 June 2022 in frequency band 10–32 MHz by the radio telescope URAN-2 are discussed in this paper. The storm was highly populated with other solar bursts, such as Type III bursts and drift pairs. The occurrence rate of S-bursts was very high reaching 60 bursts per minute. All observed S-bursts were characterized by low fluxes with respect to the background radio emission. Thus special processing methods are used to retrieve spectral properties of the bursts. Some individual “long” S-bursts covered the whole frequency band of the URAN-2 radio telescope from 10 to 32 MHz. Such extended in frequency S-bursts were recorded for the first time. 50 extended S-bursts were selected for the further analysis.Methods: The S-bursts dynamic spectra with time-frequency resolutions of 100 ms and 4 kHz as well as single-frequency profiles were used in the analysis. Due to low S-bursts intensities the drift rates were estimated from the time-differentiated dynamic spectra, highlighting the tracks of the bursts maxima. Polarization dynamic spectra were used for measuring the degree and sense of the S-bursts circular polarization. Individual S-bursts tracks were used for instant coronal inhomogeneities diagnostics. Mean S-bursts parameters retrieved from the statistical processing of the set of 50 bursts were compared with previously obtained ones.Results: We concluded that by the mean durations, drift rates, frequency extent and the polarization all observed S-bursts could be divided into two separate groups, the “short” and the “long” S-bursts. The power-law index of the drift rate-frequency dependence averaged over all 50 selected bursts was found to be 1.7. It was shown that sources of S-bursts most likely move through the Newkirk corona with the velocities of 0.06–0.08c. The power-law dependence of the “long” S-bursts durations on frequency in frequency band of 12–30 MHz was obtained. Its index equal to −0.61 appeared to be very close to that for Type III bursts. From this dependence the electron velocity dispersion in the beam, responsible for S-bursts generation was calculated. Its value of 0.02 indicates that the beams, responsible for S-bursts generation are almost monoenergetic.Discussion: It is assumed that non-monotonic appearance of individual S-bursts tracks on the dynamic spectrum reflects density inhomogeneities encountered by the sources on their paths. From the dynamic spectra of such S-bursts the characteristic size and amplitude of these coronal inhomogeneities were detected. From the S-bursts durations and the velocities of their sources the longitudinal sizes of the latter were estimated. It was then shown that the sizes of small-scale coronal inhomogeneities were comparable to those of “long” S-bursts sources. Thus we concluded that individual tracks of the “long” S-bursts can be used for fie diagnostics the coronal plasma at heliocentric heights range from 1.7 to 3.2 Rs, where Rs is the solar radius. On the other hand, these tracks being ensemble-averaged give the information about the long-term large scale properties of the corona.